Electrochemical determination of thioredoxin redox states - Dorcák, Vlastimil; Palecek, Emil (Analytical chemistry, 2009)
Thioredoxin (TRX) is a general protein disulfide reductase with a large number of biological functions, including its roles in human diseases. The TRX redox mechanism is based on reversible oxidation of two cysteine thiol groups to a disulfide, accompanied by the transfer of two protons. Using constant-current chronopotentiometric stripping analysis (CPSA) and the electrocatalytic TRX peak H, we have determined redox states of TRX at submicromolar TRX concentrations. A concentration of 1 nM TRX produces a well-developed peak H at moderate accumulation time without stirring. On the basis of this peak, interactions of 4-hydroxy-2-nonenal (HNE, product of lipid peroxidation) with TRX and the formation of TRX-HNE adducts were studied. CPSA of TRX at a carbon electrode is less sensitive and does not discriminate between reduced and oxidized forms of TRX.
Keywords: grafit; Thioredoxins; sekvence aminokyselin; rtuť; Molecular Sequence Data; Graphite; Amino Acid Sequence; proteiny z Escherichia coli; Aldehydes; Mercury; oxidace-redukce; aldehydy; molekulární sekvence - údaje; Electrodes; Oxidation-Reduction; Electrochemistry; thioredoxiny; elektrody; Carbon; uhlík; Escherichia coli Proteins; elektrochemie